Urban house price gradients in the post-COVID-19 era - Ziemann, Volker (OECD Economics Department Working Papers, 2023)
The COVID-19 pandemic has led to a significant shift in the way people work, with an increasing number of individuals opting to work from home. Fewer commutes allow people to live further away from the city centre, where jobs typically concentrate. Against this background, this paper tests the hypothesis of a shift in housing demand away from the city centre towards the suburbs using a novel granular house price data set covering 16 OECD countries. The results indicate a flattening of the house price gradients in most large urban areas with profound consequences for housing policies and the city of the future